Effects of nutrient solution and substrate on Limnocharis flava performance in hydroponic systems - RIZKA NOVI SESANTI; EDI PURWANTO; SAMANHUDI SAMANHUDI; SUDADI SUDADI (Asian Journal of Agriculture, 2025)
Abstract. Sesanti RN, Purwanto E, Samanhudi, Sudadi. 2025. Effects of nutrient solution and substrate on Limnocharis flava performance in hydroponic systems. Asian J Agric 9: 590-597. Limnocharis flava is a promising aquatic vegetable for substrate-based hydroponic cultivation. However, the optimal combination of nutrient concentrations and substrate types to maximize growth under hydroponic conditions remains unclear. This study evaluated five nutrient solution concentrations (0, 0.8, 1.6, 2.4, and 3.2 dS m-¹) and three substrate types (volcanic sand, rice husk charcoal, and a 1:1 mixture) in a Randomized Complete Block Design (RCBD) with three replications. Nutrient concentrations of 0.8 and 1.6 dS m-¹ produced the highest plant height (28.48 cm and 28.20 cm), number of leaves (11.31 and 11.03), shoot dry weight (4.61 g and 4.74 g), root fresh weight (13.20 g and 12.43 g), and root dry weight (0.76 g and 0.74 g). Both lower and higher concentrations inhibited growth, indicating optimal thresholds for nutrient uptake. Chlorophyll a, b, and total chlorophyll contents were similar across the 0.8-3.2 dS m-¹ range, but consistently higher than the control. The leaf greenness index showed a significant interaction between nutrient concentration and substrate type, with the highest value at 2.4 dS m-¹ in the mixed substrate. A nutrient concentration of 1.6 dS m-¹ produced the best overall performance. Based on these results, a combination of 1.6 dS m-¹ nutrient solution and a 1:1 mixture of volcanic sand and rice husk charcoal is recommended for the cultivation of L. flava. These findings establish baseline guidelines for hydroponic cultivation of L. flava and highlight its potential to advance precision hydroponics for indigenous vegetables, thereby contributing to food security and sustainable agriculture.